Decentralization and Urban Governance: Examining the Implementation of Regional Autonomy in Bandung Metropolitan Area (2019-2024) - Pegi Sugiartini (Journal of Political Innovation and Analysis, 2025)
This research investigates the implementation of regional autonomy in the Bandung Metropolitan Area (BMA) from 2019 to 2024, focusing on the challenges and opportunities in governance arising from decentralization. The study examines how decentralization has influenced fiscal management, public service delivery, spatial planning coordination, and inter-governmental relations within BMA, which comprises multiple autonomous local governments. The objectives include analyzing the distribution of authority and fiscal resources, assessing the effectiveness of governance in key sectors, and identifying coordination mechanisms used to address cross-jurisdictional issues. Using a mixed-methods approach, the research combines quantitative data from government reports with qualitative interviews from key governance actors. The findings reveal significant coordination failures between local governments, particularly in spatial planning and service delivery, with peripheral districts lagging the urban core. These governance pathologies are exacerbated by competing local interests and insufficient coordination frameworks. The research underscores the need for stronger metropolitan-level coordination mechanisms and fiscal equalization to address disparities between districts. Implications for policy development include recommending legal reforms to enhance metropolitan governance, particularly through the establishment of binding coordination bodies. The study contributes to the understanding of decentralization in metropolitan contexts, offering insights for other regions facing similar governance challenges.